2022
DOI: 10.1186/s40035-022-00301-5
|View full text |Cite
|
Sign up to set email alerts
|

A new paradigm for diagnosis of neurodegenerative diseases: peripheral exosomes of brain origin

Abstract: Neurodegenerative diseases are a heterogeneous group of maladies, characterized by progressive loss of neurons. These diseases involve an intricate pattern of cross-talk between different types of cells to maintain specific signaling pathways. A component of such intercellular cross-talk is the exchange of various types of extracellular vesicles (EVs). Exosomes are a subset of EVs, which are increasingly being known for the role they play in the pathogenesis and progression of neurodegenerative diseases, e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 134 publications
1
29
0
Order By: Relevance
“…The ability of exosomes from the CNS to readily cross the BBB has generated enthusiasm in their investigation as a potential biomarker source. Exosomes are considered to mirror heterogeneous biological changes that occur during the progression of neuropsychiatric diseases [ 67 ]. Animal and human studies demonstrated an accuracy of several types of exosomes and miRNAs in detecting mild, moderate, and severe traumatic brain injury [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ability of exosomes from the CNS to readily cross the BBB has generated enthusiasm in their investigation as a potential biomarker source. Exosomes are considered to mirror heterogeneous biological changes that occur during the progression of neuropsychiatric diseases [ 67 ]. Animal and human studies demonstrated an accuracy of several types of exosomes and miRNAs in detecting mild, moderate, and severe traumatic brain injury [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the CNS, glial cells, stem cells and neuron cells can secrete exosomes ( van Niel et al, 2006 ; Younas et al, 2022 ). Exosomes secreted by these cells under normal or pathological conditions can be isolated from human brain tissue and cerebrospinal fluid ( Cai et al, 2017 ; Verheul et al, 2017 ).…”
Section: The Physiological Function Of Exosomes In the Central Nervou...mentioning
confidence: 99%
“…The complex nature of TBI, compounded with inadequate scientific knowledge underpinning disease pathophysiology, poses a challenge to developing accurate diagnostic, prognostic, molecular biomarkers, and effective therapeutic modalities. The quantification of EVs as a biomarker has been investigated in studies using serum and plasma-derived EVs without sample enrichment for specific EV subtypes (Younas et al, 2022 ). The majority of attempts to establish EV-derived biomarkers of TBI have centered on leveraging the presence of traditionally investigated blood-derived proteins inside EVs for diagnosis and evaluating neurological impairments predicting the outcome (Winston et al, 2019 ; Vaughn et al, 2021 ).…”
Section: Evs As Diagnostic and Therapeutic Conduits In Tbi: Examining...mentioning
confidence: 99%